Genomic maps of some strains within the Mycoplasma mycoides cluster. - Pyle, L E (1990)
Genomic restriction maps for the small colony (SC) strains (PG1, KH3J, Gladysdale, and V5) of Mycoplasma mycoides subsp. mycoides (the agent of contagious bovine pleuropneumonia) and for Mycoplasma strain PG50 (classified as bovine serogroup 7), with respective sizes of 1,280, 1,280, 1,260, 1,230, and 1,040 kbp, were compared with the map (1,200 kbp) for a large colony strain (Y goat) of M. mycoides subsp. mycoides. The number and order of all mapped restriction sites were fully conserved in the SC genomes, as were the approximate positions of mapped loci. A number of these restriction sites in the Y genome and some, but fewer, in the PG50 genome appeared to be conserved. The SC and large colony strains shared conservation in the relative positions of the mapped loci, except for rpoC.